If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(t + 4) = 3(x + -2) Reorder the terms: 2(4 + t) = 3(x + -2) (4 * 2 + t * 2) = 3(x + -2) (8 + 2t) = 3(x + -2) Reorder the terms: 8 + 2t = 3(-2 + x) 8 + 2t = (-2 * 3 + x * 3) 8 + 2t = (-6 + 3x) Solving 8 + 2t = -6 + 3x Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + 2t = -6 + -8 + 3x Combine like terms: 8 + -8 = 0 0 + 2t = -6 + -8 + 3x 2t = -6 + -8 + 3x Combine like terms: -6 + -8 = -14 2t = -14 + 3x Divide each side by '2'. t = -7 + 1.5x Simplifying t = -7 + 1.5x
| y^4-32y^2-400=0 | | 3x/5-2=-4/5 | | -1/-2y-(y+1/4)=1/64(y-6) | | 15+.25x=20+.05x | | 4y^4-32y^2-400=0 | | x-7.1=-5.5 | | 25/2/5/6 | | 3(5h-9)=(54/6)-11h | | 3(5h-9)=9-11h | | 3x-2/4+10x-8/12=13/4+x-2/3 | | 9x-9y=2 | | 5x+7=x-5 | | 2xz-6yz-3x+9y=0 | | 6x-30y=60 | | 5qr^5= | | 2/3(2x+7)=3(3-2x)+3 | | x+3=6x-18 | | 8(2h-3)=8h+18 | | c+3+4c+3c=8+20 | | 2u^2-8u+25=u^2+1 | | u^2-8u= | | u^2-8= | | 3m+12-m=6+18-2m | | 12x+3=6x-18 | | (3x^2+3xy+3x^2y-5x+3)-(2x^2-3xy-3xy^2-2x+8)=0 | | 2x^2+16x+33=(x+5)(x+5) | | 160x+150y=190 | | 1.6x+1.5y=1.9 | | 2s+8=376 | | 7(6x+9)-2(x-4)=6+4x | | 42x+9-2x+4=6+4x | | 3x^2+5x+14=0 |